Serotonin depresses feeding behaviour in ants - Falibene, Agustina (2011)
Feeding behaviour is a complex functional system that relies on external signals and the physiological state of the animal. This is also the case in ants as they vary their feeding behaviour according to food characteristics, environmental conditions and – as they are social insects – to the colony’s requirements. The biogenic amine serotonin (5-HT) was shown to be involved in the control and modulation of many actions and processes related to feeding in both vertebrates and invertebrates. In this study, we investigated whether 5-HT affects nectar feeding in ants by analysing its effect on the sucking-pump activity. Furthermore, we studied 5-HT association with tissues and neuronal ganglia involved in feeding regulation. Our results show that 5-HT promotes a dose-dependent depression of sucrose feeding in Camponotus mus ants. Orally administered 5-HT diminished the intake rate by mainly decreasing the volume of solution taken per pump contraction, without modifying the sucrose acceptance threshold. Immunohistochemical studies all along the alimentary canal revealed 5-HT-like immunoreactive processes on the foregut (oesophagus, crop and proventriculus), while the midgut and hindgut lacked 5-HT innervation. Although the frontal and suboesophageal ganglia contained 5-HT immunoreactive cell bodies, serotonergic innervation in the sucking-pump muscles was absent. The results are discussed in the frame of a role of 5-HT in feeding control in ants.